How to raise a puppy : a dog-centric approach - Rousseau, Stephanie; Rugaas, Turid (2023)
"How to Raise a Puppy moves away from the traditional approach to raising puppies, focused on obedience and control, and instead takes a holistic, dog-centred approach. Drawing on research into how dogs naturally rear their young, and how dogs have evolved to behave and spend their time, it supports a new way of sharing our lives with our dogs. It also offers advice on dealing with some of the common challenges people experience with puppies, and tips for managing adolescence. A much-needed resource for dog trainers, veterinarians and behaviorists to recommend to clients, this conveys a powerful message to help overcome all too common issues so many people have with their puppies. Packed with practical advice, it offers an overdue "puppy perspective", with respect for a dog as a sentient being at its core"--
Keywords: Puppies; Dogs